The role of a plain dent on the failure mode of a crude oil pipeline. (April 2021) - Hafez, K.M.
Highlights: Plain dent increases fatigue stress concentration factor, and reduce fatigue life. Plain dent causes a turbulent flow of crude oil inside the pipeline. High corrosive agents with oil promote localized attack. Pipeline failure could be attributed mainly to environmentally fatigue cracking. Abstract: A failure of a subsea crude oil API 5L X52 welded steel pipeline with an 18-inch outside diameter has caused oil leakage and this event was reported after 20 years in service. Based on the post-failure investigation, it was found that there was a circumferential through-wall crack in the center of the plain dent at the leak point of the pipeline. This study investigates the role performed by the dent in the failure mode of the pipeline. Macroscopic and microscopic observation revealed that the internal surface of the pipeline contains a local erosion around the fracture zone while the outer surface contains a lot of surface cracks. The results of the investigation showed that crack was started on the outer surface at the bottom of the severely deformed (concave) zone. The concavity of the deformed pipe outer surface could result in sufficient stress cycles and residual stresses, the condition necessary for the initiation of a corrosion fatigue crack. Through thickness propagation of fatigue crack continued toward the pipe inner surface until operating stresses exceeded the yield strength of the material. As the cracks progressed, the stresses exceeded the strength of the remaining intact pipe, and a failure occurred.